Pertumbuhan dan Tingkat Kelangsungan Hidup Transplan Karang Lunak Menggunakan Metode Gantung Pada Lokasi Budidaya yang Berbeda - I Gusti Ngurah Bagus Sukertha Diputra; I Wayan Nuarsa; Widiastuti Widiastuti (Department of Marine Sciences, Faculty of Marine Science and Fisheries, Udayana University, 2021)
Besides the second largest community in the coral reef ecosystem, the attractive shapes and colors of soft corals establish it an export commodity for the marine ornamental aquarium. The transplantation methods in soft coral are limited. Commonly method for soft coral transplantation is attached to the artificial substrate followed by placed at table frame. However, this method is easily covered by algae and costly. One of the alternative methods is vertically hanging that this method commonly applied in hard corals transplantation. This study aimed to examine the average differences of growth rates among different transplanted soft coral species, different location, and the presence of interaction between soft coral species and location towards the difference of growth rates. Moreover, it determined the average survival rates among different transplanted soft coral species at different location. There were three soft coral species, Lobophytum strictum, Sinularia polydactyla and S. asterolobata. They were fragmented at initial size ± 25 cm2, hanging vertically in 1.5 m length, and 0.03 m diameter followed by located inside and outside the Pegametan bay, Sumberkima village, Buleleng Regency. The increased size of each transplanted soft coral species and the number of survivals and environmental parameters were observed every two weeks for 12 weeks. The average in growth rates among species, location, and interaction was analysed using two ways Anova, whereas the survival rates were tested using Log-Rank. Results showed that the average growth rates of transplanted soft coral inside the bay were significantly higher (4.53 cm2) than outside the bay (1.64 cm2). Moreover, the average growth rates of transplanted S. polydactyla were significantly higher than others (5.22 cm2), (respectively; 2.35 cm2 and 1.7 cm2). It was also indicated that different location and species did not differentiate the transplanted soft corals' average growth rate. The survival rates of the transplanted soft corals in different location were not significantly different as well.